A solvatofluorochromic dye as a fluorescent lifetime-based probe of β-amyloid aggregation. (June 2022) - Espinar-Barranco, Laura; Paredes, Jose Manuel; Orte, Angel; Crovetto, Luis; Garcia-Fernandez, Emilio
Abstract: In Alzheimer's disease (AD), the initial stages of the aggregation process of the β-amyloid peptide (Aβ) present a particular interest to understand the origin of the development of this disease. In this work, we present a sensor with the property of solvatofluorochromism that allows a fluorophore to undergo a shift in its emission wavelengths when placed in environments of different polarity. We used the natural adsorption binding of the dye 2-Me-4-OMe-TM, a silicon-modified xanthene derivative, to macrostructures and its solvatofluorochromic behavior to detect, in real time, modifications in the environment polarity around the dye during the initial stages of Aβ aggregation process, using steady-state, time resolved fluorescence spectroscopy and advanced fluorescence imaging techniques as fluorescence lifetime imaging microscopy (FLIM). During this progression, formation of pre-amyloid aggregates produces strong local changes in hydrophobicity that can be monitored by the fluorescent dye 2-Me-4-OMe-TM. In particular, this dye has two different emission bands and by establishing a polarity scale based on the ratiometric value of the average fluorescence lifetimes between both bands, we were able to quantify the hydrophobicity of the detected aggregates and established a method for distinguishing between aggregates of different types. Highlights: A silicon-modified xanthene derivative capable of marking amyloid aggregates. The solvatochromism of the dye allows establishing a microenvironment polarity scale. FLIM microscopy of Aβ aggregates shows different stages of the aggregation process.